Konsep Sistem OLTP pada Sistem Penjaminan Mutu Internal untuk Minimum Standar Nasional Pendidikan - Pertiwi, Asri (I-STATEMENT, 2016)
This research is aimed to represent 8 standards of Internal Quality Assurance System (SPMI) for Higher Education out of 24 standards in accordance with government regulation to Online Transactional Processing Systems (OLTP). This study uses a conceptual approach and through observation of daily activities in the case of ESQ Business School. The result will be as a solution for the software developer to develop OLTP systems of Quality Assurance in higher education so that the existence of SPMI is not only because of the necessity requirement on higher education but can provide real, actual and appropriate information.